Functional groups and common pyrolysate products of Odontopteris cantabrica (index fossil for the Cantabrian Substage, Carboniferous) - Zodrow, Eewin L (2012)
Foliage of the tree-fern Odontopteris cantabrica (Order: Medullosales) is considered a reliable plant-fossil index for the Cantabrian Substage (Carboniferous, 306 Ma). Compared are two preservation states from Canada (fossilized cuticles) and the Czech Republic (compression-cuticles), representing relatively uncommon and common preservation states, respectively. The main objective is deriving spectrochemical parameters for refining the taxonomic circumscription of the species. For the comparison, five sample categories (fossilized-cuticle, macerated fossilized-cuticle, compression, cuticle, and alkaline solution) are analyzed by methods of Fourier transform infrared (FTIR) spectroscopy, complemented by pyrolysis gas chromatography mass spectrometry (Py-GC/MS) for the Canadian sample. Variation of FTIR data in the latter sample is explained by the geochemical model for the formation of fossilized-cuticles by natural maceration.As a result, we propose a set of semi-quantitative FTIR ratios (spectral regions 1800-1000 cm-1 and 3000-2800 cm-1) as spectrochemical-taxonomic parameters for the index fossil: CH2/CH3, Al/Ox, C=O/C=C, C=O cont, Ar/Al and Ar/C=C. They contain molecular structural information related to aliphatic, aromatic and oxygen-bearing moieties. As expected, small overall spectrochemical differences occur, given converging preservation states, or similar fossilization trends for the cantabrica-plant inhabiting the Variscan Forelands of the ancestral Canada-Czech geographical regions. Some chemical differences occurred due to preservations in the sample categories (i.e., fossilized-cuticle and compression) with the oxygen-bearing structures, the length and branching of polymethylenic side chains and aromatic structures. A biomacropolymeric structure is confirmed by Py-GC/MS, and deduced for the Czech sample from the higher CH2/CH3 ratios.